Cereral Circulation in Preeclampsia - A. A. Ivshin; Ye. M. Shifman; Ye. G. Gumenyuk (Общая реаниматология, 2008)
Objective: to evaluate the possibilities of using transcranial Doppler study in pregnant women and pueperas with preeclamp-sia. Subjects and methods. Two hundred and thirty-two pregnant women diagnosed as having varying preeclampsia were prospectively studied. A comparison group comprised 90 apparently healthy women in the third trimester of pregnancy. All the respondents underwent transcranial duplex scanning of the medial cerebral artery with the linear velocity values being determined. A number of the values reflecting the level of perfusion and intracranial pressures, hydrodynamic resistance in the system, cerebrovascular responsiveness and the state of the vascular wall were calculated. Correlation analysis was made between the parameters of cerebral circulation and the severity of preeclampsia, proteinuria, the severity of hydrops, and the parameters of central and peripheral hemodynamics. Results. The findings suggest that there is impaired cerebral perfusion in pregnant women and puerperas with varying preeclampsia, the severity of cerebral circulatory disorders being in proportion with that of preeclampsia. There is a close correlation between cerebral circulation and the individual criteria determining the severity of preeclampsia. The linear values of the Doppler spectrum, namely linear flow characteristics, are prognos-tically most significant. Conclusion. The introduction of transcranial Doppler study into obstetric care has permitted the authors not only to study cerebral circulatory disorders in healthy and pregnant women and puerperas with preeclampia in detail, but also to establish a number of highly significant prognostic criteria for the severity of this life-threatening complication of gestation. The results of transcranial Doppler study assist practitioners in timely and accurately solving the problems in the diagnosis of preeclampsia and in evaluating its severity. Cerebral circulatory values may be successfully used to ascertain the efficiency of therapeutic interventions and the expediency of pregnancy prolongation. Key words: transcranial Doppler study, preeclampsia, eclampsia, cerebral circulation, severity criteria, prediction.